The Revised Kyoto Convention versus the Old One: A Capable Tool for Trade Facilitation? - Carsten Weerth (Global Trade and Customs Journal, 2010)
The World Customs Organization (WCO, Organization Mondiale des Dounaes, OMD) is an intergovernmental organization of 176 Member States that was founded as European Customs Cooperation Council in 1952. The first Kyoto Convention on simplification of customs procedures is one of its most important legal instruments. This article questions whether the Revised Kyoto Convention (RKC) is a success story, which countries are signatory countries, and whether the Developing countries are also participating in this area of trade facilitation.
Additional information: Pre-Print Data according to ROMEO/Sherpa-Database and conditions.
Keywords: K33; K34; F53; 330; World Customs Organization; Trade Facilitiation; Customs Law; Legislation; Trade Policy; Economic Law